Justice versus judiciary : justice enthroned or entangled in India? - Ranjan, Sudhanshu, 1962- (New Delhi : Oxford University Press, 2019)
There can be no dispute that the judges of the high courts and the Supreme Court of India wield tremendous powers. However, power comes with a price which bestows huge responsibility and calls for strict adherence to dos and don'ts. This text builds upon this narrative and advocates that judges must be made accountable not only in respect of their personal conduct and integrity, but also in respect of the judicial verdicts they deliver. The work emphasizes that the need for judicial accountability has increased in recent times as the judiciary is, nowadays, performing not only judicial functions, but virtually executive functions also, for which the government is accountable to the people.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 14, 2019).
Keywords: Justice, Administration of -- India; Judges -- India; Lawyers -- India; Court congestion and delay -- India; India. -- Supreme Court